2008
DOI: 10.1016/j.str.2008.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The Human Cytomegalovirus UL44 C Clamp Wraps around DNA

Abstract: Summary Processivity factors tether the catalytic subunits of DNA polymerases to DNA so that continuous synthesis of long DNA strands is possible. The human cytomegalovirus DNA polymerase subunit UL44 forms a C clamp-shaped dimer intermediate in structure between monomeric herpes simplex virus UL42, which binds DNA directly via a basic surface, and the trimeric sliding clamp PCNA, which encircles DNA. To investigate how UL44 interacts with DNA, calculations were performed in which a 12 bp DNA oligonucleotide w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 56 publications
5
31
0
Order By: Relevance
“…It should be interesting to elucidate these mechanisms. Finally, although UL44 and PCNA are structurally homologous (2), the mechanism of UL44 binding to DNA (14), the mechanism of UL54 binding to UL44 (1), and the results we present here indicate notable evolutionary divergence between UL44 and PCNA. This observation leads, in turn, to the suggestion that there may be more as-yet-unknown functions of UL44 and PCNA that the two proteins do not share.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…It should be interesting to elucidate these mechanisms. Finally, although UL44 and PCNA are structurally homologous (2), the mechanism of UL44 binding to DNA (14), the mechanism of UL54 binding to UL44 (1), and the results we present here indicate notable evolutionary divergence between UL44 and PCNA. This observation leads, in turn, to the suggestion that there may be more as-yet-unknown functions of UL44 and PCNA that the two proteins do not share.…”
Section: Discussionmentioning
confidence: 62%
“…UL44 interacts with UL54 and DNA and stimulates long-chain DNA synthesis (21,39) and thus very likely serves as a processivity factor. UL44 forms a head-to-head homodimer (1) that binds DNA without the aid of clamp loaders yet wraps around DNA akin to PCNA (14). While UL44 shows little or no sequence homology with PCNA, there is striking structural similarity between UL44 and PCNA monomers (1,2).…”
mentioning
confidence: 99%
“…BMRF1 Binds dsDNA on Its Concave Surface as a DimerThe crystal structure of the E. coli polymerase ␤-subunit revealed that dsDNA binds to the inside of the ring structure, through basic amino acid residues (44). Although there is no complex structure between DNA and a virus polymerase processivity factor available thus far, site-directed mutation analyses of HSV-1 UL42 supported the proposal that protein-DNA interactions occur with the positively charged amino acid residues on the "back" face (40).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears that HSV-1 and HCMV exhibit different requirements for the C-terminal segments of their respective accessory proteins. This and many other differences between these functionally and structurally orthologous proteins (5,6,20,24,25) suggest considerable selection for different features during evolution.…”
Section: Figmentioning
confidence: 99%